Determination of Quality of Life for Patients with Essential Hypertension: A Comparative Study - Aqeel H. Jasim (Iraqi National Journal of Nursing Specialties, 2023)
Objectives:TodeterminethequalityoflifeforpatientswithessentialhypertensioninBaghdadcity.Metliodology: A descriptive study was caried out by using a comparative design. The study was initiated fromDecember 2007 through August 2008. A multi-stage probability sampling (Stratified sampling) was used forselecting the sample settings (public medical clinics in Baghdad city). A pulposive "non-probability" sample of(400) participants; half of them were diagnosed as having essential hypellension and the other half wasnormoteusive individuals. Data were obtained through stmctured interview for both groups in a similar way, inthe same place and by the same questionnaire.A questiormaire was adopted and developed from the World Health Organization Quality of Life Scale (1998)andcon§istsofthreeparts:Sociodemographiccharacteristics,Medicaldata,andthethirdpartthatconsistofsixdomainsofqualityoflife.Validityofquestiormairewasdeterminedthrougbpresentingthequestionnaireto(15):::C£:1:tt£:Ppee:[SodanodfEee'ia#2%£¥:oq8uisrt;°unfafaear¥S]8&t:Foi8?edthroughthepilotsutywhichwascaniedData were analyzed through descriptive data analysis approach (Frequency, Percentage, Arithmetic mean,Standard deviation) and the inferential data analysis approach (Multiple Linear Regressions, K-test Z-test,Mann-Whitney test, Contingency Coefficient, Spearman correlation).Results:Theresultsrevealedthatthemajorityofbothgroupswasof(60-69)yearsoldage,married,donotreadand write, and unemployed. Most of those who diagnosed as essential hypertensive patients having disease for(6-10) years, suffering from overweight (41%), non controlling their blood pressure level (71 %), having poorqualityoflifeinphysicaldomain(P